Dynamics of territorial and political conflicts in the world - Roman Slyvka (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
Application of quantitative approach allows for gaining new results on trends of the dynamics of territorial and political conflicts (TPC). The objective of the article is to determine the dynamics in the number of territorial and political conflicts in individual macro-regions and in the whole world. The task of the article is to give grounds for viability of allocating groups of conflicts characterized by territorial manifestation from HIIK database “Conflict Barometer”; to determine the dynamics of a series of indicators typical of territorial and political conflicts in 2004-2014.